Legal analysis on the protection and development of the spotted seal population from a multi-dimensional perspective - Zhaobin Pei; Xin Sun (Archives of Community Medicine and Public Health - Peertechz Publications, 2023)
Affected by human activities, the living environment of aquatic wildlife in Bohai Bay and Huanghai Bay of our country is deteriorating day by day. In accordance with the animal protection law and other relevant laws and regulations, our country has formulated an action plan and an action plan for the protection of leopard seals. The Action Plan is based on the multi-dimensional vision of the natural environment, the balance of nature, sustainable development and human care, in 2021, the Leopard Seal is listed as a first-class protected animal in the country. This paper expounds on the survival status of the spotted seal population by searching the judgments of criminal cases, administrative cases and on-the-spot investigation on the judgment network, this paper analyzes the main reasons for the endangered population of spotted seal and puts forward the corresponding protection countermeasures.